FFT Optimizations and Performance Assessment Targeted towards Satellite and Airborne Radar Processing - Schlemon, Maron; Naghmouchi, Jamin (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2020)
Following the re-invention of the FFT algorithm by Cooley and Tukey in 1965, a lot of effort has been invested into optimization of this algorithm and all its variations. In this paper, we discuss its use and optimization for current and future radar applications, and give a brief survey on implementations that have claimed relatively high advantages in terms of performance over existing solutions. Correspondingly, we present an in-depth analysis of state-ofthe-art solutions and our own implementation that will allow the reader to evaluate the performance improvements on a fair basis. Therefore, we discuss the development of a highperformance Fast Fourier Transform (FFT) using an enhanced Radix-4 decimation in frequency (DIF) algorithm, compare it against the Fastest Fourier Transform in the West (FFTW) autotuned library as well as other solutions and frameworks.